Downlink power control for variable bit rate videos over multicell wireless networks - Yingsong Huang; Shiwen Mao (2011 Proceedings IEEE INFOCOM, 2011)
We investigate the problem of downlink power control for streaming multiple variable bit rate (VBR) videos in a multicell wireless network, where downlink capacities are limited by inter-cell interference. We adopt a deterministic model for VBR traffic that considers video frame sizes and playout buffers at the mobile users. The problem is to find the optimal transmit powers for the base stations, such that VBR video data can be delivered to mobile users without causing playout buffer underflow or overflow. We formulate a nonlinear nonconvex optimization problem and prove the condition for the existence of feasible solutions. We then develop a centralized branch-and-bound algorithm incorporating the Reformulation-Linearization Technique, which can produce (1-ε)-optimal solutions. We also propose a low-complexity distributed algorithm with fast convergence. Through simulations with VBR video traces under fading channels, we find the distributed algorithm can achieve a performance very close to that of the centralized algorithm.